Development of Technology for Sensor Chip Production with Increased Sensitivity and Improved Physical and Mechanical Characteristics for Optical Sensors Based on Surface Plasmon Resonance - Danko, V.A.; Indutnyi, I.Z.; Ushenin, Yu.V.; Lytvyn, P.M.; Minko, V.I.; Shepeliavyi, P.E.; Lykanyuk, M.V.; Korchovyi, A.A.; Khristosenko, R.V. (Science and Innovation, 2024)
An innovative project on the development of a method for manufacturing sensor chips with increased sensitivity for biosensors based on surface plasmon resonance (SPR) operating in the Kretschmann scheme has been completed. An increase in sensitivity of such sensor has been achieved by high-frequency periodic grate on the sensor chip surface formed by interference photolithography. All technology processes have been optimized. A pilot sample of modernized SPR refractometer as well as a pilot batch of nanostructured sensor chips with spatial frequencies up to 3400 mm-1 have been manufactured and tested. The use of nanostructured chips resulted in a 4.7-time increase in the SPR refractometer sensitivity.